2007
DOI: 10.1590/s1413-70542007000400018
|View full text |Cite
|
Sign up to set email alerts
|

Produção de pimentão com vibração das plantas

Abstract: RESUMORealizou-se este trabalho na Fazenda Experimental São Manuel (FCA/UNESP), município de São Manuel-SP, com o objetivo de avaliar a produção de frutos e sementes de pimentão em estufa fechada através da vibração das plantas. Foram avaliados 4 híbridos comerciais (Magali R, Margarita, Rúbia R e Elisa) e 2 tratamentos de vibração (1-sem vibração das plantas; 2-com vibração das plantas), totalizando 8 tratamentos (fatorial: 4 híbridos x 2 tratamentos de vibração), avaliados no delineamento em blocos ao acaso,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…No studies on this kind of pepper were found, thus comparing with other studies on sweet pepper in a protected environment, production was not different. CARDOSO (2007) obtained average production of 13 fruits and mass of 2,726g of fruits per plant, whereas in this experiment for sweet pepper production,the values were 24 fruits and mass of 2,242g per plant. ARAÚJO et al(2009) reported maximum number of marketable fruits per plant of 12.8, with average mass of 80g.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…No studies on this kind of pepper were found, thus comparing with other studies on sweet pepper in a protected environment, production was not different. CARDOSO (2007) obtained average production of 13 fruits and mass of 2,726g of fruits per plant, whereas in this experiment for sweet pepper production,the values were 24 fruits and mass of 2,242g per plant. ARAÚJO et al(2009) reported maximum number of marketable fruits per plant of 12.8, with average mass of 80g.…”
Section: Resultsmentioning
confidence: 50%
“…Plant vibration treatment began right after the opening of the first flower, on November 28, 2011, vibrating, manually, the wire where the bamboo cane was fixed, for about 5 seconds, twice a day, early in the morning (at 7am) and in the evening (at 5pm), until February 17 th , 2012, totaling 12 weeks of treatment. This vibration aims to release more pollen and it was adopted according to the methodology proposed by CARDOSO (2007) for sweet pepper and by HIGUTI et al (2010) for tomato.…”
Section: Methodsmentioning
confidence: 99%
“…Malpighiaceae), orange (Citrus sinensis L.; Rutaceae), lime (Citrus limon L.; Rutaceae), and various weeds. Cardozo (2007) reports that these trees, when maintained in the agroecosystem, serve to protect plants, both from pesticide drift from neighboring areas, and from the spores and/or invasive propagules. The presence of pollinators, predators, and parasitoids in the area guarantees stability of the families of insects collected in the various colored traps.…”
Section: Resultsmentioning
confidence: 99%
“…Esta correlação negativa com massa de fruto é decorrente, provavelmente, da correlação genotípica negativa entre o número de frutos por planta e a massa dos frutos. Em pimentão, em média quanto maior o número de frutos menor sua massa média (Cardoso, 2007). Já temperatura máxima, umidade relativa e insolação não se correlacionaram com os caracteres relacionados à produção.…”
Section: Resultsunclassified